The Influence of Subcultural and Personality Factors on Consumer Acculturation - Schiffman, Leon G.; Dillon, William R.; Ngumah, Festus E. (Journal of International Business Studies, 1981)
This paper explores the potential role of subcultural (religious) and personality (Rockeach Dogmatism Scale) characteristics in explaining differences in the extent of consumer acculturation. The survey results suggest that for a complex and heterogeneous nation like Nigeria, there are significant within-nation differences that may influence consumer acculturation. Implications and suggestions for future cross-cultural consumer research taking an acculturation perspective are indicated.